Performance characterization of the generic aircraft model in the NTU flight simulator - Li, Jeremy Liyan. (2009)
A study was done to evaluate the performance of the C130 model in the NTU flight simulator. The comparison was made between the performance characteristics of the generic C130 aircraft model in theory and through flight tests to affirm whether the simulator model is operating as expected. A further comparison was made with the actual C130B/C130E aircraft performance characteristics to see how well the generic model mimics the actual C130 aircraft.